Development of Quran and Hadith-Based Interactive Learning Media - Heriyanto, Imron; Rubai, Dede; Mukhlisin, Mukhlisin; Heryana, Rohman; Bustom, Ali Al; Nazriyah, Nazriyah (International Education Trend Issues, 2024)
This paper aims to develop interactive learning media based on Quran and Hadith that can be used in learning in Islamic schools. This media is designed to increase students' understanding of religious values through a more engaging and interactive approach. The research method used is the qualitative descriptive method. The results of the study show that the learning media developed is effective in increasing students' understanding of Quran and Hadith material. In addition, students also show improvement in understanding and application of the values taught in the Quran and Hadith. The development of interactive learning media based on Quran and Hadith is an effective solution to improve the quality of religious learning in Islamic schools. This media not only helps students understand religious concepts, but also supports the application of these values in daily life.